Indirect Support for a Stepwise Carbonium Ion Pathway Operating in (4+3)-Cycloaddition Reactions between Furanoxonium Ions and 1,3-Dienes - Palframan, Matthew J.; Pattenden, Gerald (Synlett, 2013)
Treatment of solutions of the furfuryl alcohol 6 in dichloromethane–methanol with buta-1,3-diene or cyclohexa-1,3-diene or with cyclopentadiene in the presence of trifluoroacetic acid leads to the corresponding substituted furyl tetrahydrofurans, 8, 12 and 15 respectively, rather than to the products 10, 13 and 16 anticipated from intermolecular (4+3)-type cycloaddition reactions. These outcomes provide indirect experimental support for a stepwise carbonium ion pathway operating in (4+3)-cycloaddition reactions between furanoxonium ions and 1,3-dienes. Alongside other results, the outcomes also highlight a limitation to (4+3) cycloadditions in cycloheptene ring synthesis when the precursors contain hydroxyl groups capable of intercepting any carbonium ion intermediates leading to O-heterocyclic by-products.
Keywords: furfuryl alcohols; (4+3)-type cycloadditions; furanoxonium ions